Hibridisasi Ikan Nila Pandu dan Kunti Generasi f5 Terhadap Efek Heterosis Ikan Nila Larasati (Oreochromis niloticus) Generasi F5 Pada Umur 5 bulan - Arief Budianto; Fajar Basuki; Sri Rejeki (Journal of Aquaculture Management and Technology, 2014)
This research aimed to compare the heterosis effect of Larasati Tilapia from F5 generation the growth variable weight, length, thickness, survival rate and food convertion ratio, for ♂ Larasati F5, ♂ Pandu F5, ♂ Kunti F5; and ♀ Larasati F5, ♀ Pandu F5, ♀ Kunti F5 at the age of 5 month. This research was conducted in Freshwater Hatchery and Aquaculture Unit Janti, Klaten. Larasati Tilapia F5 generation, Pandu Tilapia F5 generation, and Kunti Tilapia F5 generation at the age of 4 months. This research were used 3 treatments and 3 replications for each sex. The treatment used was Larasati Tilapia F5, Pandu Tilapia F5, and Kunti Tilapia F5 generation. The result show that growth of Tilapia Larasati F5 generation was better than the parent generation Tilapia Pandu F5 generations and Tilapia Kunti F5 generations. Heterosis value of Larasati Tilapia F5 generation at the age of 5 months were, weight of (♂) 31.45% and (♀) 26.94% . Length of (♂) 22.90% and (♀) 19.96%. Thick of (♂) 22.84% and (♀) 19.88%. Survival rate of (♂) 1.33% and (♀) 1.48%. Food convertion ratio of (♂) -0.76% and (♀) -0.68%.